A New Sea Surface Roughness Parameterization and Its Application in Tropical Cyclone Modeling. Issue 24 (25th December 2022) - Lan, Y.; Sun, D.; Leng, H.; Song, J.; Cao, X.; Dong, R.
Abstract: The intensity simulation of tropical cyclones (TCs) has been a long‐standing challenge for numerical models, and an accurate sea surface roughness ( z 0 z_0 ) parameterization scheme is the key to enhance the intensity prediction. In our study, a new z 0 z_0 parameterization scheme (SD21) is proposed and applied in the Coupled Ocean‐Atmosphere‐Wave‐Sediment Transport model to simulate two super typhoons. The SD21 takes into account both the wave state and sea foam, and it is suitable for low to extreme wind conditions. The results of the eight numerical experiments show that the TC intensity and structure are sensitive to the choice of z 0 z_0 parameterization schemes. Compared with the widely used z 0 z_0 parameterization schemes, the SD21 scheme presents much better results in the simulation of the intensity and intensification speed of strong TCs. Notably, the simulation of the wind speeds generated by the SD21 is more compatible with the best track data and significantly better than that of the other schemes. Furthermore, we find that the wave state and sea foam remarkably affect the magnitude and spatial distribution of z 0 z_0, the following two conclusions are obtained: (a) The z 0 z_0 parameterization that takes into account the wave state can reduce the excessive roughness at the TC periphery and restrict the high‐value area of the roughness to the TC‐core region. (b) The sea foam significantly decreases the roughness value in areas with 10 m wind speeds above 40 m/s. Plain Language Summary: In nature, tropical cyclones are a destructive weather phenomenon. The strong winds that occur during these cyclones lead to the intense exchange of the air‐sea momentum flux. The momentum flux will directly affect the intensity and structure of a TC. Additionally, the momentum flux exchange depends on the sea surface roughness; thus, proposing a more accurate parameterization scheme of the sea surface roughness is significant for accurately predicting TCs with numerical models. This study proposed a new roughness parameterization scheme that considers the wave age, wave steepness and sea foam. The roughness that is calculated under high wind speeds by this scheme can also be very consistent with the experimental and field observation data. In this study, the parameterization scheme is applied to the Coupled Ocean‐Atmosphere‐Wave‐Sediment Transport model to simulate the two super typhoons, Mangkhut and Yutu. Compared with the existing parametric schemes, this scheme significantly improves the simulation results of TC intensity and structure. Key Points: A new sea surface roughness parameterization scheme that considers the wave state and sea foam is proposed and applied to a coupled model The wave state and sea foam can affect the transmission of the air‐sea momentum flux by changing the sea surface roughness The sea foam reduces the values of the sea surface roughness in the core region of TC and significantly optimizes the simulation of a TC